Trans ambulatory: profile of users and demands for occupational therapy (Research, Society and Development, 2022)
The daily reality of trans people goes through variables that are determined by historical, social and cultural conditions and affect their ways of living and forms of social participation. The general objective of this work is to understand the profile and demands for Occupational Therapy, of the users of the Transgender Comprehensive Health Outpatient Clinic of the Federal University of Sergipe. This is a cross-sectional and descriptive study in a service for trans people in a city on the interior of the State of Sergipe. Data regarding the profile of users were collected from Occupational Therapy assessment sheets to the profile of users carried out in the period from 2016 to July 2021. The population profiles are of people who on the average are people with 23 years old, live in Aracaju, have completed high school, have a good/normal relationship with their mother, live with primary family members and are allocated underemployment. They have culinary skills and manual skills, maintain leisure activities and have as life projects the possibility of traveling and working with a formal bond. Literature tells us that a good part of trans people are in prostitution spaces, which does not corroborate the findings of this research, when we observe, for example, data related to trans people and work experiences.